Mapping the Alterations of Glutamate Using Glu-Weighted CEST MRI in a Rat Model of Fatigue - Li, Ruili; Dai, Zhuozhi; Hu, Di; Zeng, Haiyan; Fang, Zeman; Zhuang, Zerui; Xu, Haiyun; Huang, Qingjun; Cui, Yilong; Zhang, Handi (Frontiers in Neurology, 2020)
Objective: Glutamate dysregulation may play an important role in the pathophysiology of fatigue. Glutamate weighted chemical exchange saturation transfer (Glu-weighted CEST) MRI is a recently developed technology which enables measuring glutamate in vivo with high sensitivity and spatial resolution. The purpose of this study is to map the alternations of brain glutamate in a rat model of fatigue. Methods: Rats were subjected to ten days fatigue loading procedure (fatigue group) or reared without any fatigue loading (control group). Spontaneous activities of rats in the fatigue group were recorded from 3 days before fatigue loading to 4 days after the end of fatigue loading. Glu-weighted CEST were performed following 10-day fatigue loading. Results: Rats in the fatigue group exhibited significant reduced spontaneous activities after 10-day fatigue loading. The glutamate level in the whole brain increased significantly in the fatigue group compared to that in the control group. Further analysis of glutamate in the sub-regions of brain including the prefrontal cortex, hippocampus and striatum revealed a trend of increment, although statistic significance was not reached. Significance: The increase of glutamate level in the brain may be a crucial process involved in the pathophysiology of fatigue.